PENGARUH LATIHAN LONCAT-LOMPAT TETRAGONAL TERHADAP KELINCAHAN SERTA KECEPATAN LARI SIWA SMU - Dapan Dapan (Jurnal Kependidikan, 1999)
Abstract The purpose of this study is to determine the effect of clock-wise and counter clock wise tetragonal jump on agility and sprint of senior high school students. The population of this research is male students of the Senior High School 12 Yogyakarta. The sample random sampling technique is utilized to select 75 students as the sample of this study. They are divided into two treatment groups and control groups. The data were analyzed by Anacova at significant level of 5%. This study concludes that the clock-wise tetragonal jump is more effective in increasing agility than counter clock-wise one. However, both clock-wise and counter clock wise tetragonal jump do not have significant effect on sprint. Keywords: tetragonal jump, agility, and sprint